Extratos de canola e própolis no controle de oídio em pepineiro - Piva, Claudia Aparecida Guginski (2013)
Powdery mildew, caused by the fungus Podosphaera fuliginea, is a disease of universal occurrence, considered one of the most common among cucurbits. All species are susceptible, but the severity depends on the type of climate, species and cultivars. In the culture of cucumber (Cucumis sativus L. Cucumins) powdery mildew causes damage mainly in greenhouses, necessitating the use of toxic products in your control. The interest in alternative methods of control is growing, including the biological, organic or natural alternatives to present efficient control, with features like the low potential for contamination to the environment, the health of the operator and the consumer. Experiments were conducted in a greenhouse and repeated in two crops, using canola and própolis extracts to control powdery mildew in cucumber. In the first experiment was tested the potential effect of powder canola (Brassica napus L.) extracts in four forms of extraction: alcoholic, infusion, maceration and aqueous extract and five concentrations of each extract: 0, 3, 6, 9 and 12%. The first application was made 24 hours before the pathogen inoculation and other weekly for a period of 5 weeks, measuring the incidence and severity of disease and the elicitor effect of extracts in the induction of resistance by the enzyme phenylalanine ammonia lyase (FAL), total phenolics and total proteins. In the second experiment was tested the effect of ethanol propolis extract applied in different times and concentrations: 24 hours before the pathogen inoculation, 24 hours after pathogen inoculation and the appearance of the firsts disease symptoms with 0% (distilled water); 0,5; 1; 2; 4 and 8% of the extract. In the first experiment, there was a higher activity of FAL and greater accumulation of phenolic compounds, which are parameters related to the reduction of AUDPC for the incidence and severity of powdery mildew, highlighting how the best to control the maceration extract at a concentration of 12%, with reduced more than 50% incidence and more than 90% disease severity. In the second experiment it was found that a própolis aqueous extract applied 24 hours before and 24 hours after the inoculation of the pathogen gave better control of AUDPC the incidence and severity when compared to aplication in the first disease symptoms. This effect was more significant when it was used at a concentration of 8%. The results in both experiments showed that the powder canola extract, as well as the alcoholic própolis extract, have potential for control of powdery mildew on cucumber.